Immunization during pregnancy: do healthcare workers recommend vaccination against influenza? - Francesca Licata; Concetta Paola Pelullo; Giorgia Della Polla; Emma Antonia Citrino; Aida Bianco (Frontiers Media S.A., 2023)
BackgroundA variety of circumstances can influence how widely vaccination during pregnancy is accepted. Healthcare workers (HCWs) are often seen as the main resource for recommending vaccination. The purpose of the current study was to determine whether Italian HCWs advise and recommend pregnant people to receive the influenza vaccinations, as well as what knowledge and attitudes affect their practices. A secondary aim of the study was to evaluate HCWs' knowledge and attitudes towards COVID-19 vaccination.MethodsThis cross-sectional study, took place between August 2021 and June 2022 in a randomly selected sample of HCWs in three Italian regions. The target population comprised obstetricians-gynecologists, midwives and primary care physicians, who provide medical care to pregnant people. The questionnaire consisted of 19 items divided into 5 parts gathered information about the participants' sociodemographic and professional characteristics, general knowledge about vaccinations during pregnancy, and vaccine-preventable diseases (VPDs), attitudes and practices towards immunization, and strategies to potentially increase vaccination uptake during pregnancy.ResultsAmong the participants, 78.3% knew that pregnant people are at increased risk of severe complications from influenza, 57.8% that the influenza vaccine is not provided only in the 2nd/3rd trimester of pregnancy and 60% that pregnancy is a risk factor for severe COVID-19 infection. Of the enrolled HCWs, 10.8% believed that the potential risks of vaccines administered during pregnancy are greater than the benefits. An even higher proportion of the participants was unsure (24.3%) or did not deem (15.9%) that vaccinating against influenza during pregnancy reduces the risk of preterm birth and abortion. Moreover, 11.8% of the sample did not believe or was uncertain that COVID-19 vaccine must be offered to all pregnant people. Among HCWs, 71.8% advised women about influenza vaccination during pregnancy, and 68.8% recommended getting vaccinated against influenza during pregnancy. Results showed that good knowledge and positive attitudes were the strongest factors positively associated with advising women about influenza vaccination during pregnancy.ConclusionThe gathered data showed that a sizable portion of the HCWs lacks up-to-date knowledge, underestimates the risks of contracting a VPD, and overestimates the risks of vaccine side effects during pregnancy. The findings shed light on such attributes useful to promote adherence to evidence-based recommendations among HCWs.